An analysis of the possible fiscal consequences of a controlled foreign company being declared resident in South Africa– may SARS have its cake and eat it? - Kotze, Salmon Ruan (Department of Commercial Law, 2020)
The issue considered in this paper proceeds from the basis of a hypothetical income tax assessment issued by SARS against a hypothetical taxpayer. The circumstances under which the hypothetical assessment is raised are as follows: suppose that Company A, a South African resident, owns 100% of the participation rights in Company B (the hypothetical taxpayer), a resident of Luxembourg. Company A has failed to qualify for any of the internal “exemptions”1 contained in section 9D of the Income Tax Act, 58 of 1962 (“the Act”), and has thus been taxed with reference to the profits of Company B for the past ten years. In the eleventh year, SARS audits Company B and determines that its effective place of management has, in fact, been in South Africa all along and that it is therefore resident in South Africa in terms of paragraph (b) of the definition of “resident” contained in section 1 of the Act. Upon the determination that Company B is resident in South Africa, SARS proceeds to raise assessments against Company B in relation to the taxable income it earned during its current and former years of assessment (i.e. income tax assessments are raised for the full 11-year audit period) (referred to herein below as the “hypothetical assessment”). The purpose of this paper is thus to investigate the fiscal consequences that do (and, it will be argued, do not) arise subsequent to a controlled foreign company (“CFC”) having been declared resident of the Republic of South Africa, in circumstances where a South African resident taxpayer had historically been taxed with reference to the profits of that CFC in terms of section 9D. It is clear from the example that the same income now being taxed in the hands of Company B subsequent to its South African residency would already have been taxed in the hands of Company A by application of section 9D. The inequity of this result is undeniable. Should assessments be raised against Company B in the manner suggested it would amount to economic double taxation.